Case report: A novel case of parental mosaicism in SMC1A gene causes inherited Cornelia de Lange syndrome - Gil-Salvador, Marta; Latorre-Pellicer, Ana; Lucia-Campos, Cristina; Arnedo, María; Darnaude, María Teresa; Díaz de Bustamante, Aránzazu; Villares, Rebeca; Palma Milla, Carmen; Puisac, Beatriz; Musio, Antonio; Ramos, Feliciano J.; Pié, Juan (Frontiers in Genetics, 2022)
Ultimate advances in genetic technologies have permitted the detection of transmitted cases of congenital diseases due to parental gonadosomatic mosaicism. Regarding Cornelia de Lange syndrome (CdLS), up to date, only a few cases are known to follow this inheritance pattern. However, the high prevalence of somatic mosaicism recently reported in this syndrome (~13%), together with the disparity observed in tissue distribution of the causal variant, suggests that its prevalence in this disorder could be underestimated. Here, we report a new case of parental gonadosomatic mosaicism in SMC1A gene that causes inherited CdLS, in which the mother of the patient carries the causative variant in very low allele frequencies in buccal swab and blood. While the affected child presents with typical CdLS phenotype, his mother does not show any clinical manifestations. As regards SMC1A, the difficulty of clinical identification of carrier females has been already recognized, as well as the gender differences observed in CdLS expressivity when the causal variant is found in this gene. Currently, the use of DNA deep-sequencing techniques is highly recommended when it comes to molecular diagnosis of patients, as well as in co-segregation studies. These enable us to uncover gonadosomatic mosaic events in asymptomatic or oligosymptomatic parents that had been overlooked so far, which might have great implications regarding genetic counselling for recurrence risk.